2015
DOI: 10.1111/1440-1681.12339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inflammatory factor‐induced cyclo‐oxygenase expression on the development of reperfusion‐related no‐reflow phenomenon in acute myocardial infarction

Abstract: SUMMARYNo reflow after reperfusion therapy for myocardial infarction is a strong predictor of clinical outcome. Increased levels of inflammatory factors, including C-reactive protein (CRP), in patients with acute myocardial infarction (AMI) undergoing primary percutaneous coronary intervention (PCI) may affect myocardial perfusion. However, why the no-reflow phenomenon increases in inflammation stress after PCI is not clear. The aim of the present study was to determine the effects and molecular mechanisms und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
(130 reference statements)
0
6
0
Order By: Relevance
“…41 Experimental research revealed that CRP can promote the development of the no-reflow phenomenon by increasing cyclooxygenase-1 and cyclooxygenase-2 expression, which is regulated, in part, via extracellular signal-regulated kinase and Jun N-terminal kinase activity. 42…”
Section: Discussionmentioning
confidence: 99%
“…41 Experimental research revealed that CRP can promote the development of the no-reflow phenomenon by increasing cyclooxygenase-1 and cyclooxygenase-2 expression, which is regulated, in part, via extracellular signal-regulated kinase and Jun N-terminal kinase activity. 42…”
Section: Discussionmentioning
confidence: 99%
“…Jiao reported that elevated CRP increases the expression of cyclooxygenase, in a time‐ and concentration‐dependent manner, resulting in NRP 29 . However, Niccoli found no significant correlation between CRP serum levels on admission and coronary artery NRP 30 …”
Section: Discussionmentioning
confidence: 98%
“…29 However, Niccoli found no significant correlation between CRP serum levels on admission and coronary artery NRP. 30 The underlying reason for the negative result may be that the sample size of the study was relatively small. Our study suggested that the CRP level, WBC, neutrophil to HDL-C ratio and monocyte to HDL-C ratio at admission in the hyperuricaemia group were higher than those in the non-hyperuricaemia group.…”
Section: Discussionmentioning
confidence: 99%
“…Factors secreted by neutrophils which include ROS, cytokines, and chemokines which promote inflammation may also damage previously viable tissue [ 68 ]. Neutrophils obstruct post-capillary venules contributing to microvascular dysfunction [ 85 ] which is thought to mediate no-reflow phenomenon associated with reperfusion injury [ 68 , 85 , 87 ]. Platelets recruited to sites of injury may also contribute to reperfusion injury and microvascular dysfunction by secreting vasoactive thromboxane A 2 and 5-HT.…”
Section: Cardiac Physiology and Pathologymentioning
confidence: 99%